Pemanfaatan Maltodextrin Singkong untuk Perekat Ramah Lingkungan dalam Pembuatan Papan Partikel dari Bagas Sorgum (Utilization of Cassava Maltodextrin for Eco-friendly Adhesive in the Manufacturing of Sorghum Bagasse Particleboard) - Sutiawan, Jajang; Hermawan, Dede; Kusumah, Sukma Surya; Widyaningrum, Bernadeta Ayu; Sukara, Endang (Jurnal Sylva Lestari, 2020)
The development of natural adhesives derived from non-fossil resources is very important for the future. This research aimed to develop natural adhesive from maltodextrin and compare it with other natural adhesives such as citric acid and malic acid for particleboard production. The effect of the adhesive raw materials on the physical and mechanical properties of the particleboards was investigated. The sweet sorghum and those natural adhesives were used in the manufacturing of particleboard. The resin content of the natural adhesive was 20 wt% base on air-dried particles. The dimension and density target of the boards were 30 x 30 x 0.9 cm3 and 0.8 g/cm3, respectively. The particleboards were prepared by hot pressing at 200°C for 10 min. The physical and mechanical properties of particleboards were evaluated based on Japanese Industrial Standard for particleboard (JIS A 5908-2003). The results showed that the density, moisture content, modulus of elasticity, and modulus of rupture met the requirements of the JIS A 5908-2003 standard, while the thickness swelling, water absorption, and internal bond did not meet the standard requirements. The results of FTIR analysis indicated the establishment of ester linkages due to the reaction between the natural adhesive and sorghum bagasse that contributed to the excellent physical and mechanical properties of the particleboard. Keywords: cassava, maltodextrin, natural adhesive, particleboard, sweet sorghum